Cuticular and Medullary Structure of Some Wild Herbivores of India - Charjan, Rupali; Nadeshwar, NC; Banubakode, SB; Kurkure, NV; Bonde, SV (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The dorsal guard hair is considered as a mammalian exoskeleton. The anatomical feature of the three concentric layers of the mammalian hair, viz., medulla, cortex, and cuticle vary considerably with different species. The characteristics features of cuticular scales and medullary pattern can be used as an important tool for species identification by using various methods for hair analysis. The morphological features of cuticle and medulla of dorsal guard hair samples of Sambar (Rusa unicolor), Nilgai/blue bull (Boselaphus tragocamelus) and Spotted deer (Axix axis), six each, were studied during post-mortem examination. The microscopic studies showed a difference in some of the cuticular scale and medullar cells among three species. Hence, a single morphological feature of hair may not be a confirmative tool for species identification but multiple morphological features can be used as a confirmative tool of species identification. This study provides pictographic details in eead of some wild species which can be used to curb criminal acts against wild animals.